Characterization of the blob generation region and blobby transport in a stellarator. (15th April 2016) - Fuchert, G; Birkenmeier, G; Ramisch, M; Stroth, U
Abstract: Filaments of increased pressure ('blobs') in the scrape-off layer of toroidally confined magnetized plasmas are studied in the context of fusion research due to their relevance for confinement and wall safety. Analytical models in simple toroidal magnetic field geometries have proven useful to get a quantitative understanding of blob dynamics in tokamaks. However, their direct applicability to the more complicated stellarator geometry is far less studied. The experiments presented here show that in the stellarator TJ-K blobs are field-aligned structures occurring in scrape-off layer regions of negative mean normal curvature, which is in agreement with common blob models. Furthermore, it is shown that in TJ-K, in accordance with findings from tokamaks, blobs account for a significant fraction of the turbulent scrape-off layer transport of the order of several tens of percent.